Babylon in comics - Battini , Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2025)
Babylon is one of the most common themes in comics about ancient Mesopotamia. Only one of the city’s eras is usually represented. And of all the city’s extraordinary monuments, the Tower of Babel (actually a ziqqurat, or temple) or the Hanging Gardens (which were not in Babylon but in Assyria) have particularly caught the eye.